2021
DOI: 10.1101/2021.08.15.456391
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantifying predator functional responses under field conditions reveals interactive effects of temperature and interference with sex and stage

Abstract: Predator functional responses describe predator feeding rates and are a core component of predator-prey theory. Although originally defined as the relationship between predator feeding rates and prey densities, it is now well known that predator functional responses are shaped by a multitude of factors. Unfortunately, how these factors interact with one another remains unclear, as widely used laboratory methods for measuring functional responses are generally logistically constrained to examining a few factors… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…All data and code for their analyses are permanently archived on Zenodo https://doi.org/10.5281/zenodo.6426222 (Coblentz, 2022).…”
Section: Data Availability Statementmentioning
confidence: 99%
“…All data and code for their analyses are permanently archived on Zenodo https://doi.org/10.5281/zenodo.6426222 (Coblentz, 2022).…”
Section: Data Availability Statementmentioning
confidence: 99%
“…Gilg et al, 2006;Messier, 1994;Moleón et al, 2012;Moustahfid et al, 2010;Nielsen, 1999;Nilsen et al, 2009). However, other studies show saturated feeding rates at only one or a few observations at the highest observed prey densities (Angerbjörn, 1989;Coblentz et al, 2022;Korpimaki & Norrdahl, 1991;Quinn et al, 2003;Redpath & Thirgood, 1999;Sundell et al, 2000) or little to no evidence of feeding rate saturation (Beardsell et al, 2021(Beardsell et al, , 2022Coblentz et al, 2021;Novak, 2010;Novak et al, 2017;Preston et al, 2018). Therefore, it is currently unclear how saturated feeding rates are likely to be in general.…”
Section: Introductionmentioning
confidence: 99%